Building a Sustainable Seafood System for Maine - Alden, Robin (Maine Policy Review, 2011)
In this article, Robin Alden notes that Maine could have one of the premier marine food systems in the world. However, that means adequate stewardship of the Gulf of Maine ecosystem and diversifying the fishing industry beyond lobster by creating innovative public policy and a food system that supports community fishing.